1981
DOI: 10.2337/diab.30.12.1000
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Insulin on the Disposal of Intravenous Glucose: Results from Indirect Calorimetry and Hepatic and Femoral Venous Catheterization

Abstract: The effect of insulin on the disposal of intravenous glucose was examined employing the euglycemic insulin clamp technique in 24 normal subjects. When the plasma insulin concentration was raised by approximately 100 μU/ml, total glucose metabolism rose to 6.63 ± 0.38 mg/kg · min. Basal splanchnic (hepatic venous catheter technique) glucose production, 2.00 increased only slightly. These results suggest that the ability of higher doses of insulin to further stimulate glucose metabolism is primarily the result o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
950
5
11

Year Published

1995
1995
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,604 publications
(996 citation statements)
references
References 0 publications
30
950
5
11
Order By: Relevance
“…Among the best-documented responses in skeletal muscle to insulin are the activation of glucose transport and the Na,KATPase [1][2][3][4]. Skeletal muscle expresses both the GLUT1 and GLUT4 glucose transporters but it is the mobilization of GLUT4, from an intracellular store to the plasma membrane (PM), that explains the observed increase in glucose transport in response to insulin binding [5][6][7][8].…”
Section: Introduction 2 Materials and Methodsmentioning
confidence: 99%
“…Among the best-documented responses in skeletal muscle to insulin are the activation of glucose transport and the Na,KATPase [1][2][3][4]. Skeletal muscle expresses both the GLUT1 and GLUT4 glucose transporters but it is the mobilization of GLUT4, from an intracellular store to the plasma membrane (PM), that explains the observed increase in glucose transport in response to insulin binding [5][6][7][8].…”
Section: Introduction 2 Materials and Methodsmentioning
confidence: 99%
“…a reduced glucose disposal and impaired inhibition of hepatic glucose output at a given concentration of insulin (McGarry, 2002). A major contribution to whole-body insulin resistance comes from the skeletal muscle, as revealed by classical work by DeFronzo et al (1981), who have shown a 45% reduction in leg glucose uptake following a hyperinsulinaemic euglycaemic clamp in patients with type 2 diabetes and a strong positive correlation (r 0 . 70, P <0 .…”
Section: Intramyocellular Lipid and Insulin Sensitivitymentioning
confidence: 99%
“…Another possibility that accounts for the reduced insulin sensitivity among those detrained female young dancers was the reduction in skeletal muscle GLUT4 protein expression. Skeletal muscle is the main tissue for postprandial glucose disposal, 19 while GLUT4 protein is the main isoform of glucose transporter expressed in skeletal muscle. This protein has been found to be elevated by exercise 20 and downregulated following short-term detraining.…”
Section: Detrained Dancers Exhibit Increased Insulin S-y Chen Et Almentioning
confidence: 99%